Conventional and Non-conventional Smoking on Microbial Quality and Histamine of Ikan Fufu (Smoked Fish) (International Journal of Scientific Research and Management (IJSRM), 2021)
Fish is a commodity with high nutritional value. The content of this nutritional value causes fish to be easy to decompose. Therefore, it is necessary to develop and process skipjack fufu (smoked skipjack) fish that improve the quality of smoked skipjack tuna (smoked skipjack) chemically, microbiologically, and with low histamine content. The purpose of this study was to determine the chemical, microbiological, and histamine quality of smoked fish with conventional and non-conventional smoking. This type of research was a quantitative study with a randomized block design. This research is a laboratory experiment with two treatments, namely conventional and non-conventional methods equipped with three replications and three blocks. The results of the test on the third day (H3) and the ninth day (H9) of storage showed that there was no growth of Salmonella sp. and Vibrio cholera in smoked fish samples with conventional (P2) and non-conventional (P1) smoking techniques. There were differences in non-conventional and conventional smoking on the histamine content in smoked fish. Conclusion. There was no growth of Salmonella sp and Vibrio cholera in smoked fish. There is a difference in the histamine content of conventional (P2) and non-conventional (P1) smoking techniques in smoked fish.